The Leadership Role of The Visionary and TransformationalSchoolPrincipalat MIS Al-Husna YPIHN and MIS Miftahul Khaer - Nurhanifah, Nurhanifah (Universitas Negeri Malang, 2024)
This research aims to determine the role of visionary and transformational school principal leadership in implementing the vision and mission in improving the quality of teaching and education staff. As well as to find out the obstacles to the school principal's visionary and transformational leadership in implementing the vision and mission in improving the quality of teaching and education staff. This research method uses qualitative methods. Research was conducted at MIS Al-Husna YPIHN and MIS Miftahul Khaer. Data collection methods use interview, observation and documentation techniques. The results of the research show that the visionary and transformational leadership of the principal at MIS Al-Husna YPIHN in implementing the vision and mission to improve the quality of teaching and educational staff is carried out by (1) increasing pedagogical competence, (2) teacher personality competence, (3) teacher social competence, (4) increasing teacher professionalism, (5) monitoring and evaluation activities. Meanwhile, MIS Miftahul Khaer carries it out starting from analyzing deficiencies, teachers' needs from external and internal factors and improving teachers' tasks, to planning programs to overcome deficiencies and problems faced by teachers. The obstacles to implementing improving the quality of educational energy by the head of MIS Al-Husna YPIHN Tangerang District are (1) lack of teacher experience, (2) lack of experience in communication techniques, (3) the number of productive female teachers. Meanwhile, the obstacles faced by the head of MIS Miftahul Khaer are limited facilities, the commitment of good teachers and the lack of teacher experience, good experience in the field of review material.